2007
DOI: 10.1007/s00246-007-9010-5
|View full text |Cite
|
Sign up to set email alerts
|

Results of 100 Consecutive Extracardiac Conduit Fontan Operations

Abstract: Throughout the years, the experience with Fontan's operation has increased and has opened the way to a much wider application of this principle. A number of major risk factors have been identified and managed by several modifications of the original Fontan procedure. In the past 15 years, operative and postoperative risks have been controlled to a major extent by the application of intermediate surgical procedures. Modifications to the original technique have been designed to simplify surgery and better protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This finding is in contrast to a study byBalaji 9 et al, where no difference regarding pacemaker implantation was found, but in line with the results reported by Downing et al, who also found an association between LT and need for pacemaker 6. EC type TCPC, which minimizes the ischemic time and atrial suture lines, has been suggested to reduce the incidence of atrial tachycardia 11. However, as the surgical procedure switched from LT to EC in Sweden beginning in 1998, we cannot yet estimate the long-term need for a pacemaker in patients who received an extracardiac tunnel.…”
supporting
confidence: 85%
“…This finding is in contrast to a study byBalaji 9 et al, where no difference regarding pacemaker implantation was found, but in line with the results reported by Downing et al, who also found an association between LT and need for pacemaker 6. EC type TCPC, which minimizes the ischemic time and atrial suture lines, has been suggested to reduce the incidence of atrial tachycardia 11. However, as the surgical procedure switched from LT to EC in Sweden beginning in 1998, we cannot yet estimate the long-term need for a pacemaker in patients who received an extracardiac tunnel.…”
supporting
confidence: 85%
“…Although some patients may remain as unreparied or palliated single ventricle, the standard cardiovascular surgical approach to patients with a univentricular heart is a staged repair to a Fontan procedure. The Fontan surgery has undergone multiple modifications from the initial atrail appendage to pulmonary artery anastamosis, to the lateral tunnel, to the more recent extracardiac conduit 1–10 . From an electrophysiologic viewpoint, over half of these patients will develop a cardiac rhythm abnormality 5–10 years after the Fontan procedure 1–22 .…”
Section: Introductionmentioning
confidence: 99%
“…Total cavopulmonary connection (TCPC) represents an efficient palliative surgery in single‐ventricle pathologies . TCPC produces a unique physiology in which pulmonary blood flow is driven primarily by the residual force of the systemic ventricle, causing a substantial increase of systemic venous pressure.…”
mentioning
confidence: 99%